Peran Gaya Kepemimpinan Transformasional Terhadap Kinerja Aparatur Sipil Negara : Tinjauan Teoritis dan Empiris - Sandya Ananda Maisa; Liski Lestari; Yuri Khairunnisa (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine theoretically and empirically the role of transformational leadership style on the performance of the State Civil Apparatus (ASN), especially in the context of bureaucratic reform. Using a literature review approach, the discussion is focused on understanding the concept of transformational leadership, the performance dimensions of ASN, the theoretical relationship between the two, and its implications in efforts to improve the quality of public services and governance. The results of the study show that transformational leadership contributes positively to improving the performance of ASN through motivation, empowerment, and the creation of a shared vision. This leadership style also presents its own challenges in a hierarchical bureaucracy, but still offers effective strategies for building a transformative and professional organizational culture. This research provides a conceptual basis for efforts to strengthen leadership in the public sector as part of the ongoing bureaucratic reform agenda.